Biodiversity and Systematic Conservation Planning for the Twenty-first Century: A Philosophical Perspective - Sarkar, Sahotra (Conservation Science, 2015)
The concept of biodiversity, its introduction in conservation biology, and its evolution in the framework of systematic conservation planning, are analyzed. Attempts to quantify biodiversity and to find surrogate measures for it are described. It is shown that biodiversity originated as and remains a fundamentally normative concept. However, while attempts to reduce biodiversity conservation to the achievement of sustainability are misplaced, natural values other than biodiversity also merit promotion. Multi-criteria analysis can be used to capture necessary trade-offs between these values when they are in conflict. Moreover, given the possibility of trade-off analysis, socio-cultural values can also be integrated into habitat use decisions along with natural values. Thus biodiversity conservation can be integrated into more general framework of habitat use planning. Conservation Science Vol.2(1) 2014: 1-11